Agroecology and social sciences: challenges for a paradigmatic transition in agri-food production - Cerdas Vega, Gerardo Enrique (2025)
The essay argues for the need to reconsider the role and contribution of social sciences in the transition towards a new paradigm for agri-food production, which implies a shift from the model of industrial agriculture towards agroecology. In order to provide a contextual perspective of the required change, a systemic perspective is adopted, highlighting the potential of agroecology as a transdisciplinary approach to drive this transformation. It concludes by highlighting various areas where the social sciences can contribute to a necessary change in the way food is produced, exchanged, and consumed, which is fundamental to our collective existence.